Crystal growth and some physicochemical studies on an organic intermolecular compound of anthranilic acid and N,N-dimethylamino benzaldehyde - Rai, Uma Shanker; Singh, Manjeet; Rai, Rama Nand (European Journal of Chemistry, 2018)
The phase diagram of anthranilic acid and N,N-dimethylaminobenzaldehyde system gives two eutectics (E1 and E2) and a 1:1 intermolecular compound with congruent melting point. The mole fractions of anthranilic acid at E1 and E2 are 0.10 and 0.95, respectively. The negative values of heat of mixing of eutectics suggest that there is clustering of molecules in their eutectic liquid melt. The positive values of excess free energy for eutectics indicate that the interactions between the like molecules are stronger than those of unlike molecules. It can be inferred from single crystal X-ray analysis of the intermolecular compound that it crystallized in monoclinic unit cell with C2/c space group and a reasonably large sized intermolecular compound crystal was grown by slow evaporation technique at room temperature. The optical studies on the intermolecular compound give two strong emission bands with two lmax values one at 380 nm and second at 450 nm with total quantum efficiency 0.49.